Alzheimer’s disease manifests abnormal sphingolipid metabolism - Uranbileg, Baasanjav; Isago, Hideaki; Sakai, Eri; Kubota, Masayuki; Saito, Yuko; Kurano, Makoto (Frontiers in Aging Neuroscience, 2024)
Investigating the association of disturbed metabolism with Alzheimer's disease (AD), we focused on sphingolipids due to their known physiological impact on various diseases. Our aim was to understand the possible role of sphingolipids in AD's pathogenesis and pathology by conducting comprehensive profiling. Sphingolipid levels were measured in AD brains, Cerad score B brains, and controls, and in iPS cells (AD, PS, and control) using liquid chromatography mass spectrometry.AD brains showed higher sphingosine (Sph), total ceramide 1-phosphate (Cer1P), and total ceramide (Cer) levels than control and Cerad-B brains. Deoxy-Cer was elevated in Cerad-B and AD brains compared to controls, with increased sphingomyelin (SM) levels exclusively in Cerad-B brains. Cell lysate analysis revealed elevated dhSph, total Cer1P, and total SM in AD and PS cells versus controls. Multivariate analysis emphasized Sph, Cer, Cer1P, and SM relevance in AD pathology. Machine learning highlighted Sph, Cer, and Cer1P as key contributors to AD. These findings suggested the potential importance of Sph, Cer1P, Cer, and SM in the context of AD pathology.